Intervensi Penanganan Psikologis pada Pengguna NAPZA - Khasanah, Widya Nur; Anshori, Rika Oktaviani; Lestari, Prita; Aryanti, Khofifah; Maulani, Zulviana Nurahma; Farida, Reica Vina; Hasan, Laila Azmila; Sunari, Tia Bella; Hilmayasari, Rizma; Rohmawati, Rohmawati; Carolin, Wafa Nabiilah; Verdyan, Nesya Pradini; Hendrita, Noni; Sianturi, Renta (Jurnal Kesehatan Holistic, 2022)
Introduction: Drug abuse is a problem that occurs at the national, regional and global levels. Drug dependence can lead to psychological effects such as emotions, violent behavior, insecurity, depression, and so on. Psychological impacts due to drug dependence can be handled in the form of treatment, rehabilitation or other interventions. Written articles using a Literature Review approach to 11 articles on psychological treatment of drug abuse in the 2017-2021 period using the keywords "Psychological treatment", "Drug abuse", "Self-efficacy", "Therapeutic community" With the aim of knowing the effectiveness of psychological treatment for drug users. Based on the results obtained in psychological treatment of drug abuse from 11 articles in the form of therapeutic community intervention, ablution therapy, expressive writing, cognitive behavioral therapy, motivational interviewing, yoga therapy, group education, logotherapy can improve positive aspects in patients with drug abuse and can reduce the impact or psychological symptoms and dependence on drug users. The advantages obtained from various nursing interventions can help treat or rehabilitate drug users, but from the results of the study there are some limitations in the application of interventions to the treatment.